Apneic Oxygenation during Rapid Sequence Intubation in Critically Ill Children - Mortimer, Todd; Burzynski, Jeff; Kesselman, Murray; Vallance, Jeff; Hansen, Gregory (Journal of Pediatric Intensive Care, 2016)
This prospective case series documented hypoxemia and potential complications associated with apneic oxygenation in critically ill pediatric patients during rapid sequence intubation. Forty-four patients received apneic oxygenation via nasal cannula at rates of 5, 10, and 15 L/min for ages <4, 4 to 12, and 12 to 18 years, respectively. Pre- and postintubation attempt mean Spo2 were 98.9 ± 2.95 and 90.7 ± 1.95%, respectively. Postintubation Spo2 < 80% were significantly less with one intubation attempt, compared with multiple attempts (p < 0.001). No serious complications were noted. Apneic oxygenation was well tolerated in critically ill children.
Keywords: apneic oxygenation; hypoxemia; airway management